Regeneration through decay: Architectural prosthetic within the damaged coastline of the South African West Coast - Coetzee, Flavio (Faculty of Engineering and the Built Environment, 2023)
The relationship between decay and regeneration acts as a theoretic foundation from which this dissertation suggests a new method of approaching architecture that allows for a perspectival shift. International large scale sand mining industries along the West Coast of South Africa resulted in collapsed dune and natural systems impacting the livelihoods of small dependent communities. Approved mining permits South of the sensitive Oifants River Estuary risks a complete collapse of the ecological equilibrium. Simulating damage once mining operations are complete lead to the discovery of the last most important portion (the pinch point). This landscape lends itself as a testing ground for an architectural investigation acting as a tool to stabalise the pinch point, rehabilitate ecology and serve as resistance for any future exploitation. Using the Japanese practice of Kintsugi the project tests whether architecture can act as an adhesive that restores and elevates the value of scars left within the landscape. Through testing conceptual ideas of permanence and impermanence this results in a speculative design which is nestled within the impacts of time. Stretching the potential of architecture to become an extension of the landscape itself, whilst dissolving silently as if it never existed becoming a form of structure. Through acting with and against the forces of nature beyond the site boundaries, the architecture is placed in a constant state of transmutation.